Shot Peening Effect on Fatigue Crack Repaired Weldments - J. Efrain Rodriguez-Sanchez; Alejandro Rodriguez-Castellanos; Faustino Perez-Guerrero (Advances in Materials Science and Engineering)
Fracture mechanics calculations are required to validate the safety level defined in design codes to prevent a fatigue failure. The periodic inspection-assessment cycle can lead to the implementation of a fatigue crack repair by crack removal. To improve the fatigue performance of the crack repair, residual compressive stresses induced by peening can be considered. This paper is in relation to the peening effect estimation on stress intensity factors in fatigue crack repaired weldments, since the stress intensity factor is a key parameter in fracture mechanics calculations. A set of T-butt specimens were experimentally fatigue tested and crack propagation data was gathered for the calculation of stress intensity factors. The experiments were designed to estimate the residual compressive stress depth layer and its effect on crack propagation inhibition. Experimental estimation of the peening effect on stress intensity factors in fatigue crack repaired weldments was validated by comparison against an analytical weight function solution. Experimental stress intensity factors determined from a set of fatigue tested T-butt specimens allowed estimating preliminarily that peening has a limited effect on fatigue crack propagation inhibition for edge repaired T-butt weldments subjected to bending loading.